BVLOS UAV missions for vegetation mapping in maritime Antarctic - Zmarz, Anna; Karlsen, Stein Rune; Kycko, Marlena; Korczak-Abshire, Małgorzata; Gołębiowska, Izabela; Karsznia, Izabela; Chwedorzewska, Katarzyna (Frontiers in Environmental Science, 2023)
Polar areas are among the regions where climate change occurs faster than most other areas on Earth. To study the climate change effects on vegetation there is a need for knowledge about its current status and properties. Both classic field observation methods and remote sensing methods, based on manned aircraft or satellite image analysis have limitations. These include high logistic operation costs, limited research areas, high safety risks, direct human impact, and insufficient resolution of satellite images. Fixed-wing UAV BVLOS missions can bridge the scale gap between field-based observations and full-scale airborne or satellite surveys. Operations of the unmanned aerial vehicle beyond the visual line of sight (UAV BVLOS), at an altitude of 350 m ASL, have been successfully performed in Antarctic conditions. Maps of the vegetation of the western shore of Admiralty Bay (King George Island, South Shetlands, Western Antarctic) including the Antarctic Specially Protected Area No. 128 (ASPA 128) were designed. The vegetation in 7.5 km2 was mapped with ultra-high resolution (<5 cm and DEM of 0.25 m GSD) and from the Normalized Difference Vegetation Index (NDVI), four broad vegetation units were extracted: "dense moss carpets" (cover 0.14 km2, 0.8 % ASPA 128), "Sanionia uncinata moss bed" (0.31 km2, 1.7% of ASAP 128), "Deschampsia antarctica grass meadow" (0.24 km2, 1.3% of ASAP 128), "Deschampsia antarctica - Usnea antarctica heath" (1.66 km2, 9.4 % of ASAP 128). The presented UAV BVLOS-based surveys are time-effective (single flight lasting 2.5 hours on a distance of 300 km) and cost-effective compared to classical field-based observations, and less invasive for the ecosystem. Moreover, unmanned airborne significantly improves security, which is of particular interest in polar regions research. Therefore their development is highly recommended for monitoring areas in remote, fragile environments.